Answer:
[tex]\frac{15}{4}[/tex]
Step-by-step explanation:
P(2 heads) = P(first flip = head)*P(second flip = head)
=> [tex](\frac{1}{2} )(\frac{1}{2} )[/tex] = [tex]\frac{1}{4}[/tex]
P(1 head) = P(first flip = head)*P(second flip = tail) + P(first flip = tail)*P(second flip = head)
= [tex]\frac{1}{4} +\frac{1}{4} =\frac{1}{2}[/tex]
P(no heads) = P(first flip = tail)*P(second flip = tail)
= [tex]\frac{1}{4}[/tex]
E(winning) =[tex]10(\frac{1}{4} )+0(\frac{1}{2} )+5 (\frac{1}{4} )[/tex]
= [tex](\frac{10}{4} )+ (\frac{5}{4} )[/tex]
= [tex]\frac{15}{4}[/tex]